Data Management in Grid and Peer-to-Peer Systems Third International Conference, Globe 2010, Bilbao, Spain, September 1-2, 2010, Proceedings - Hameurlain, Abdelkader.; Hameurlain, Abdelkader.; Morvan, Franck.; Morvan, Franck.; Tjoa, A Min.; Tjoa, A Min. (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
Since 2008, Globe has been an annual international conference on data management in grid and peer-to-peer systems. Initially, grid and peer-to-peer systems experienced significant success in scientific and file sharing applications. Today, these systems cover the management of large, distributed and heterogeneous data. These systems are characterized by high heterogeneity, high autonomy and dynamics of nodes, dec- tralization of control and large-scale distribution of resources. Research on data m- agement in grid and peer-to-peer, relatively recent, aims to scale distributed systems and applications that require effective management of voluminous, large-scale distr- uted and heterogeneous data. The third edition of the international conference Globe was held in Bilbao, Spain during September 1-2, 2010. Globe provided opportunities for academia or industry researchers to present and discuss the latest research and applications on data m- agement in grid and peer-to-peer systems. Globe 2010 received 26 papers from 15 countries. The reviewing process led to the acceptance of 13 papers for presentation at the conference and inclusion in this LNCS volume. Each paper was reviewed by at least two Program Committee members. The conference would not have been possible without the support of the Program Committee members, external reviewers, Organizing Committee, members of the DEXA conference and the authors. In particular, we would like to thank Gabriela Wagner and Roland Wagner (FAW, University of Linz) for their help in the reali- tion of this conference.